SIKAP ADOPSI E-COMMERCE DAN DAMPAKNYA TERHADAP KEPUASAN KONSUMEN PADA TOKO BATIK LENGO LAWEYAN SURAKARTA - Shinta Mardiana Dewi; Marti Wahyu Setiawan (STIE Atma Bhakti, 2022)
This study aims to analyze the influence of e-commerce perceptions, perceived quality, and external factors on e-commerce adoption attitudes and their impact on consumer satisfaction. The research used a survey method conducted on consumers of Batik Lengo Laweyan Surakarta shops related to e-commerce perceptions, perceived quality, and external factors on attitudes towards e-commerce adoption and consumer satisfaction at Batik Lengo Laweyan Surakarta shops. Data collection techniques using literature studies, questionnaires and interviews. The population in this study is all consumers who make purchases using e-commerce at the Lengo Laweyan Batik Store, Surakarta. The sample in this study were 110 respondents. The data analysis technique used in this study uses path analysis (critical path). The findings in this study are perceptions of e-commerce and external factors that have a positive and significant impact on e-commerce adoption attitudes and have a positive and significant impact on consumer satisfaction, while perceived quality has a negative and insignificant impact on e-commerce adoption attitudes and satisfaction. consumer. E-commerce adoption attitudes mediate the effect of external factors on consumer satisfaction, and non-e-commerce adoption attitudes mediate the effect of e-commerce perceptions and perceived quality on consumer satisfaction.